2019
DOI: 10.1111/ijpo.12589
|View full text |Cite
|
Sign up to set email alerts
|

Total and trimester‐specific gestational weight gain and infant anthropometric outcomes at birth and 6 months in low‐income Hispanic families

Abstract: Objective To describe total and trimester‐specific gestational weight gain (GWG) among low‐income Hispanic women and determine whether these GWG exposures are associated with infant anthropometric outcomes at birth and 6 months. Study Design Data were from 448 mother‐infant pairs enrolled in the Starting Early child obesity prevention trial. Prenatal weights were used to calculate total GWG and 2nd and 3rd trimester GWG rates (kg/week) and categorized as inadequate, adequate, and excessive according to the 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Thus, GWG rate is preferable for exploring the relationship between trimester-specific weight change and infant birth weight even though the data collection is complicated. The overall prevalence of insufficient and excessive GWG rate varies in different regions [8,9]. Some studies showed that 12.5 and 57.9% of Chinese women had insufficient and excessive GWG rate respectively in 2013 [10], but the updated incidence rate is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, GWG rate is preferable for exploring the relationship between trimester-specific weight change and infant birth weight even though the data collection is complicated. The overall prevalence of insufficient and excessive GWG rate varies in different regions [8,9]. Some studies showed that 12.5 and 57.9% of Chinese women had insufficient and excessive GWG rate respectively in 2013 [10], but the updated incidence rate is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most research in China is province-based or city-based and lacks representativeness. As for the association between GWG rate and birth weight, relevant studies are even mere, and the results are also inconsistent [8,16]. Furthermore, few studies have explored the dose-response relationship between women's body weight before or during pregnancy and infant birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…Latina women are at higher risk for excessive or inadequate weight gain compared with non-Hispanic women ( Deirelein et al, 2020 ). Previous studies suggest similar to our own findings that higher risk for excessive weight gain in Latinas is associated with pre-pregnancy overweight or obese status ( Dolin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We had a relatively small percentage of our overall sample size that reported gestational gain below the IOM guidelines for adequate weight gain, a risk factor for low birthweight and preterm birth. As such, we did not assess or evaluate risk factors for low gestational weight gain in contrast with other studies with urban Latinas that have found a higher percentage of inadequate gain in their cohorts ( Deirelein et al, 2020 ). Our population was primarily foreign-born (Mexico and Central America) and with less than a high school education level.…”
Section: Conclusion and Limitationsmentioning
confidence: 94%
“…Greater maternal pre-pregnancy weight and GWG were associated with higher systolic blood pressure (36), adverse accumulation of lipid and inflammatory profiles (9,44), increased risk of congenital heart disease (19,45), myocardial hypertrophy (16), hypertension (15), and premature death in later life in the offspring (46,47). The GWG in the second and third trimesters accounted for a majority of the total GWG and played an important role in offspring growth, adiposity, and metabolic state (48). It was a key period for organ development, including the heart, muscles, bones, and liver (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%